Crescimento urbano-industrial e a dinâmica migratória na Região Metropolitana da Grande Vitória (1960-2010): as particularidades socioespaciais dos impactos no município da Serra - Silva, Madson Gonçalves da (2015)
Analyzes the sharp urban-industrial growth of 1960-2010 in the Metropolitan Region of Great Vitória, relating it with migration and the socio-spatial developments seen in this period. Also points out that the implementation of the "Large industrial projects", in the late 1960s, correlated to a regional, national and global stage, which placed the Espírito Santo in the global economy. It is part of the research line "State and Public Policy", the MA in Social History of Political Relations. Presents as a problem the relationship between industrialization process with migration in the metropolitan region of Great Vitória and how the socio-spatial effects of this interaction can be observed in the municipality of Serra. Believes that there is an intense process of industrialization which was associated with urbanization in the capital and surrounding municipalities, providing an abrupt population growth not accompanied by public policies of the State, which intensified the social and spatial inequalities. It aims to relate industrial development and urban growth to migration from an analysis that shows the “overdeterminations” of the effects of this process through sociospatial inequality indicators and homicides, focusing, in the municipality of Serra.